2016
DOI: 10.1007/s40011-016-0706-2
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Pretreatment Decreases Absorption of Phenacetin (Cytochrome P450 1A2 Substrate), Without Altering its Disposition Kinetics in Rats

Abstract: Many drugs used in the therapeutic regimen for various ailments undergo metabolism via cytochrome P450 1A2 (CYP1A2), so the agents or conditions altering the expression and/or activity of this enzyme play a significant role in therapeutic efficacy/failure of its substrates. Though curcumin is reported to be an inhibitor of CYP1A2, influence of curcumin on the pharmacokinetics of CYP1A2 probe phenacetin in rats has not yet been published to the best of our knowledge. Hence an attempt has been made to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…However, curcumin treatment could promote the recovery of normal functionality and morphology of the duodenum. It indicated that consumption of feed containing AFB1 would result in decreased nutrient digestion and absorption capacity of chickens, but curcumin could alleviate the AFB1-induced intestinal toxicity; these results were in according with previous studies ( Prasad et al, 2017 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, curcumin treatment could promote the recovery of normal functionality and morphology of the duodenum. It indicated that consumption of feed containing AFB1 would result in decreased nutrient digestion and absorption capacity of chickens, but curcumin could alleviate the AFB1-induced intestinal toxicity; these results were in according with previous studies ( Prasad et al, 2017 ).…”
Section: Discussionsupporting
confidence: 87%
“…AFB1 is extremely toxic, and has carcinogenic, teratogenic, and mutagenic effects on mammals and poultry ( Kalpana et al., 2012 ). It has been reported that duck fed on maize naturally contaminated with AFB1 had a negative effect on intestinal function and morphology, and altered digestive physiology and growth performance ( Prasad et al., 2016 ). In the present study, histopathological examination revealed that AFB1 could induce significant alteration in the functionality and morphology of the duodenum, including histological lesions, increase the length of the duodenum and the depth of the crypt, decrease the unit weight of the duodenum, the height of villus, and the value of V/C.…”
Section: Discussionmentioning
confidence: 99%